Exploring the relationship between Corporate Social Responsibility (CSR) and Organisational Profitability-A study of the UAE Manufacturing Industry - Jahan Ibrahim Alrajawy, Sarwat (International Journal of Psychosocial Rehabilitation, 2020)
Corporate social responsibility (CSR) is an important and strategic tool for an organization to maintain its sustainability and create a trustworthy and good image in the market as well as for its customers. The rationale of the CSR and organization’s profitability is that all of the enterprises gain their benefits from the society; that is why the organizations are required to return the benefits in other ways back to the society and the environment. This research is about examining the impact of corporate social responsibility (CSR) on organizational profitability, and the research shows that CSR has a positive impact on the organization’s profit. The sample size for this research is 150 for conducting the survey from the employees of the UAE manufacturing industry, and the sample size is 10 for the interviews conducted from the managers of the industry. Both primary and secondary sources of information are used, and a mixed approach of qualitative and quantitative analysis is considered. The quantitative analysis for this research is based on the correlation, regression, and descriptive analysis to show the link between the variables, and the intensity of their relationship is also determined, and the qualitative research design is thematically analyzed.